2015
DOI: 10.1186/s12939-015-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Labor and delivery service use: indigenous women’s preference and the health sector response in the Chiapas Highlands of Mexico

Abstract: BackgroundMexico has undertaken important efforts to decrease maternal mortality. Health authorities have introduced intercultural innovations to address barriersfaced by indigenous women accessing professional maternal and delivery services. This study examines, from the perspective of indigenous women, the barriers andfacilitators of labor and delivery care services in a context of intercultural and allopathic innovations.MethodsThis is an exploratory study using a qualitative approach of discourse analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…However, unlike these countries, no targeted intercultural health care service for Indigenous women was found in the CHT and often these women experienced discrimination (including unofficial payments and abusive treatment) from health staff, including Indigenous health staff, at the public facilities. As with previous studies, this study found that Indigenous women lacked knowledge about existing primary health facilities and about the importance of accessing MHC services [36][37][38]. These findings are supported by literature that state the importance of relatives and neighbours, may provide incomplete information regarding ANC and facility delivery [47][48][49].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, unlike these countries, no targeted intercultural health care service for Indigenous women was found in the CHT and often these women experienced discrimination (including unofficial payments and abusive treatment) from health staff, including Indigenous health staff, at the public facilities. As with previous studies, this study found that Indigenous women lacked knowledge about existing primary health facilities and about the importance of accessing MHC services [36][37][38]. These findings are supported by literature that state the importance of relatives and neighbours, may provide incomplete information regarding ANC and facility delivery [47][48][49].…”
Section: Discussionsupporting
confidence: 86%
“…Indigenous women in the CHT reported that pregnancy was a natural event. MHC services were perceived to be essential to access only if a woman was experiencing "somossya" (complications) during pregnancy and at childbirth, when situations became uncontrollable and were beyond the capacity of a TBA [36,37,48,50,51]. Otherwise, MHC services were considered a waste of time and money.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reveal that Indigenous peoples perceived pregnancy and delivery as ‘natural events’, and would only visit health facilities if the situation becomes out of control 21 23 25 26. CHT Indigenous women with knowledge of pregnancy-related complications were more likely to access MHC services during pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 98%
“…Distance to services, language barriers and cost are key barriers for Indigenous women accessing existing MHC services 20–25. The top-down nature of health intervention programmes can make services culturally unfriendly for Indigenous women in lower and middle income countries, impacting their access to available services 26.…”
Section: Introductionmentioning
confidence: 99%